Productive performance of the fattening and slaughter of horses and mares finished on grazing - Paredes, Manuel (2022)
The aim of this study was to evaluate the productive performance of fattening and slaughter of creole horses and mares of 10-11 years of age, finished on grazing and slaughtered after six weeks of fattening. Ten horses and 10 mares were used. The productive performance was not affected by the sex of the animal. Average daily weight gain (0.628 and 0.678 kg), dry matter intake (6.91 and 6.95 kg), feed conversion (11.4 and 11.3), carcass yield (47.6 and 44.9%) and meat yield (37.4 and 37.9%), was obtained in males and females, respectively.